INVESTIGATIVE ANALYSIS OF ULTRASOUND THERAPY ON PHYSIOTHERAPY SERVICES IN THE STATE OF PERNAMBUCO (Fiep Bulletin - online, 2013)
Ultrasound was introduced in therapeutic practice between 1930 and 1940 as a thermotherapy resource capable of producing intense heat. Ultrasounds generated can transmit their energy in two pulse regimes, continuous or pulsed. The transmission of an ultrasound wave comes from an applicator head; the gel is the best coupling medium for releasing ultrasound's energy. Most professionals responsible for TUS, today, ignore the un-standardized state. Investigate the quality of ultrasound therapy in the state of Pernambuco physiotherapy services. The sample will have 49 physiotherapy services from the state of Pernambuco where the apparent state of TUS equipments and their maintenance were both analyzed following a questionnaire and salt spray test performance. The study showed that 87% of services were private and 13% public; 59% of TUS equipments from physiotherapy services good and 31% fair. Results obtained upon checking equipments adjustment, and the Test of fog performance, showed that 13% of them had a fog under 1.1 w/cm2 ; 28% between 1.1 w/cm2 and 1.5 w/cm2; 28% with the intensity above 1.5 w/cm2. About 31% of businesses presented equipments in which the fog was not apparent. Our results showed that TUS equipments in the state of Pernambuco physiotherapy services are giving an incorrect dosimeter, which suggests that they are lacking standard qualities established by technical norms.
Keywords: Quality; Test of Fog; Therapeutic Ultrasound